Modelo de Interacción Inteligente del Reglamento del Congreso de Colombia para Dispositivos Móviles - Pinzon Ortiz, Jesus Emilsen; Espinel Ortega, Alvaro; Ramos Sandoval, Olga Lucia (Ingeniería, 2020)
Context: There is no technological system for mobile devices, which interacts naturally with the user and provides a precise answer to any question related to the Regulations of the Congress. The present work establishes an “Intelligent Interactive Model of the Regulations of the Colombian Congress for mobile devices” MIRC; and to achieve this, it is implemented in an app app. Method:The proposed Interaction Model is based on the Information Recovery Model (Architecture of a Natural Language Processing System). However, it was necessary to include several structural changes in the sense that as the system must process the user's voice and respond with synthesized voice, it was necessary to emulate several processes that facilitate the interaction of the mobile with the user. Results:an MIRC app “Intelligent Interactive Model of the Congress Regulations for mobile devices” is delivered, adjusted to requirements suggested by several users (without disabilities and with disabilities); In general, very useful for its ease of consultation on issues of the Regulation. Conclusions: The objective of delivering an MIRC app was fulfilled, through an Intelligent Interaction Model for consulting the Congress Regulations, using the PLN Natural Language Programming. Where the user interacts with the mobile device, using his voice to make a request and the answer is given to the device in digital voice.